Analisis Kesesuaian dan Daya Dukung Ekowisata Kategori Wisata Pantai di Pantai Pulau Merah Banyuwangi - Ahmad, Fuad Hasin; Restu, I Wayan; Wijayanti, Ni Putu Putri (Current Trends in Aquatic Science, 2020)
The study aimed to determine the tourism suitability index and carrying capacity of Red Island Beach. The study was carried out using descriptive method. The study used purposive sampling to determine the tourism suitability index, while the data used for determination of tourism carying capacity was collected directly using QGIS software. The data was colledted from 3 stations along the Red Island Beach, and the distance of each station was 1000 m. The distance of sampling from the beach was 10 m, and performed in triplicate. Parameters measured in this study were: water depth, beach type, beach width, substrate type, water current, slope, water sharpness, land cover, dangerous biota, and freshwater availability. The results showed that the value of the tourism suitability index from 3 stations was categorized into S1 (Very Suitable) (IKW> 80%). The result indicates that the beach of Red Island Banyuwangi can support the development of recreational beach activities. As for the value of the support of the area divided into 2 categories, for the tourism category of recreational beaches obtained the value of carrying capacity of 1,500 people/day, swimming category obtained the value of the support of 240 people/day. It could be concluded that carrying capacity of Red Island Beach is categorized as under carrying capacity. The visitor should be increased up to 36% to reach a balance tourism visit.